Are Continuous Femoral Nerve Catheters Beneficial for Pain Management After Operative Fixation of Tibial Plateau Fractures? A Randomized Controlled Trial. Issue 12 (December 2019) - Cooke, Margaret E.; Welch, Tyler; Gusakov, Oleg; Tornetta, Paul
Abstract : Objective: To determine whether a continuous femoral nerve block after open reduction internal fixation of tibial plateau fractures would diminish Visual Analog Scale (VAS) scores and/or systemic narcotic intake. Design: Randomized controlled trial. Setting: Level 1 academic trauma center. Patients: Forty-two consecutive patients with operatively treated tibial plateau fractures. Intervention: Continuous femoral nerve catheter for postoperative pain management was performed in the experimental group. Main Outcome Measures: Both the VAS scores for pain and narcotic intake were assessed at 4, 8, 12, 24, 36, 48, and 72 hours postoperatively. Results: Forty-two patients were enrolled in this study. There were 21 women and 21 men 21-70 years of age (avg 49) with operatively treated tibial plateau fractures. Twenty-one patients were randomized to receive a femoral nerve block with 5 crossovers for technical reasons. Accordingly, we analyzed 16 patients with femoral nerve blocks and 26 with standard care. There were no significant differences between the study groups regarding age, sex, or fracture type. There was no significant difference in VAS scores between the control and experimental group at any time point. The total systemic morphine equivalent for the femoral nerve block group and the control group was 375 and 397 respectively ( P = 0.76). Across groups, patients with bicondylar fractures tended to have higher VAS than those with unicondylar fractures and to use more narcotics, although neither was statistically significant. Conclusion: Femoral nerve blocks for postoperative pain management in tibial plateau fractures did not demonstrate an improvement in pain relief or narcotic use. Level of Evidence: Therapeutic Level I. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.